Continence after BNR in the complete repair of bladder exstrophy (CPRE): A single institution expanded experience. Issue 4 (August 2020) - Di Carlo, Heather N.; Manyevitch, Roni; Wu, Wayland J.; Maruf, Mahir; Michaud, Jason; Friedlander, Daniel; Gearhart, John P.
Summary: Introduction: Several surgical methods have been used for primary repair of bladder exstrophy in the newborn. Complete primary repair of exstrophy (CPRE) aims to prevent the need for surgeries beyond the newborn period. Due to the rarity of bladder exstrophy, it has proven difficult in the past to analyze whether use of this method of closure truly does confer acceptable continence outcomes and hence minimizes the requirement for additional surgeries later in life. Objective: To describe the continence outcomes of CPRE patients who went on to receive bladder neck reconstruction (BNR), and secondarily, to compare clinical features between those patients who were able to receive undergo a BNR compared to those who were not. Study design: An IRB approved database of 1330 exstrophy-epispadias patients was used to identify referred patients after successful CPRE for management of continued urinary incontinence. Urinary continence outcomes were assessed in those who underwent modified Young Dees Leadbetter BNR following CPRE. Results: Sixty-one patients were referred for treatment after successful CPRE between 1996 and 2016. None developed continence or a dry interval after primary closure. Of these, forty-two (68.9%) underwent BNR by a single surgeon at a mean age of 5.8 years (range 5–8.4). The mean bladder capacity at BNR was 147 mL (range 102–210 mL). Twenty-five (59.5%) achieved day and night continence, 7 (16.7%) gained daytime continence with nocturnal leakage, and 10 (23.8%) remain totally incontinent. Mean follow-up after BNR was 5.9 years. Combined CPRE and pelvic osteotomy were performed in 100% of patients who were continent and 75% of those who were daytime dry. No continent patient had a ureteral reimplantation before BNR, whereas 4 patients with daytime continence and nocturnal leakage and 7 patients who remained continuously incontinent did. Discussion: This is the largest known series of BNRs in exstrophy patients closed by CPRE. Previous smaller studies have demonstrated mild to moderate success rates of BNR after CPRE, with many patients still requiring additional continence surgeries. The present study found similar results, with additional indication that successful primary closure and use of pelvic osteotomies may correlate with enhanced continence. This study includes outcomes from a single surgeon, with a maximum length of follow up of 13 years. Conclusions: CPRE alone often does not render patients continent of urine, based on the authors' referral population. However, following BNR continence rates in this subgroup were found to reach 76%. Surgeons who treat this population should keep these factors in mind when planning continence surgeries. Summary Table Patient demographics and outcomes of the 61 patients referred to the authors' institution after undergoing a successful complete primary repair of exstrophy (CPRE). (Abbreviations: VC fistula, vesicocutaneous fistula; UC fistula, urethrocutaneous fistula; URI, ureteral reimplant; YDL BNR, modified Young-Dees-Leadbetter bladder neck reconstruction; BNT, bladder neck transection; CS, continent stoma.) Summary Table Characteristic N (%) Gender   Male 49 (80.3%)   Female 12 (19.7%) Surgeon type   Pediatric surgeon 10 (16.4%)   General/adult urologist 6 (9.8%)   Pediatric urologist 45 (73.8%) Additional Genitourinary Surgeries   VC fistula 3 (4.9%)   UC fistula 14 (22.9%)   URI 17 (27.9%)   Hypospadias repair 34 (69.4%) YDL BNR 42 (68.9%)   Day and nighttime continence 25 (59.5%)   Daytime continence, nocturnal leakage 7 (16.7%)   Total incontinence 10 (23.8%) Mean age at BNR, years (range) 5.8 (5–8.4) Mean bladder capacity at BNR, cc (range) 147 (102–210) BNT, augment, CS 12 (19.7%)